Meningkatkan Berpikir Kritis Dan Kerjasama Siswa Muatan Matematika Menggunakan Model Panting Kelas V Sekolah Dasar - Yeny Marliani; Noorhapizah Noorhapizah; Akhmad Riandy Agusta; Tika Puspita Widya Rini (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study is a classroom action research aimed at improving students' critical thinking and collaboration skills through the PANTING model. The research was conducted in Class V of SD Negeri Belitung Selatan 2 Banjarmasin during the even semester of the 2024/2025 academic year, involving a total of 20 students, consisting of 11 boys and 9 girls. The study was carried out over four meetings, and data collection was conducted through direct observation during the learning process. The collected data were then analyzed using observation sheets, with the success indicators being the improvement in students' critical thinking and collaboration skills in each session. The results showed a significant increase in students' critical thinking skills from 50% "less skilled" to 85% "very skilled", and their collaboration skills improved from 45% "less skilled" to 85%. Therefore, it can be concluded that the implementation of the PANTING model can enhance students' critical thinking and collaboration skills.